FICTIONAL NARRATIVE AS A COUNTER-NARRATIVE OF IDENTITY POLITICS IN THE NOVEL “DARI DALAM KUBUR” BY SOE TJEN MARCHING: A POSTCOLONIAL APPROACH - Saraswati, Rina (Prosiding Konferensi Internasional Kesusasteraan, 2025)
This study examines Soe Tjen Marching’s Dari Dalam Kubur (From Inside the Grave) as a fictional narrative that functions as a counter-narrative to hegemonic identity politics in post-1965 Indonesia. The research background stems from the dominance of the official New Order narrative, which stigmatized certain groups—particularly those associated with the Indonesian Communist Party, ethnic Chinese, and political activists—through exclusionary and discriminatory identity constructions. Fiction, in this context, is positioned as an alternative medium capable of challenging the dominant discourse by offering a humanist and inclusive perspective. This study employs a descriptive qualitative method by collecting the data through close reading and note-taking. The data are analyzed using content analysis with a postcolonial approach. Using a postcolonial theoretical framework, specifically the concepts of Third Space, in-betweenness, and hybridity by Homi K. Bhabha; the voice of the subaltern by Gayatri Spivak; and orientalism by Edward Said, this study examines the narrative strategies used by the novel to represent marginalized and subaltern identities. The analysis shows that the novel constructs a space for cultural resistance through the re-presentation of personal memories, depicting the complexities of victim identities, and dismantling the state-constructed "other."